Unprecedented : the constitutional challenge to Obamacare - Blackman, Josh (Josh M.) (New York : PublicAffairs, 2013)
" This inside story of the legal challenge to Obamacare from a conservative constitutional lawyer involved in the movement is a brilliant mixture of legal, political, and media intrigue capped by a truly consequential Supreme Court decision"--
"On November 13, 2009, Josh Blackman and a group of Federalist Society lawyers gathered in a Washington, DC, hotel to devise a legal challenge to Obamacare. It seemed a very long shot and was dismissively ignored by the White House, much of Congress, and all of the media. Two years later, the fight to overturn the Affordable Care Act had grown fierce and the government's case was tottering. When, finally, the Supreme Court announced its ruling their judgment was so surprising that two cable news channels misunderstood it and announced that the Act had been deemed unconstitutional"--
Includes index.
Keywords: United States; National health insurance -- Law and legislation -- United States; Health care reform -- United States; Health insurance -- Law and legislation -- United States; Medical care -- Law and legislation -- United States; Constitutional law -- United States; Medical care -- United States -- Cost control; LAW / Constitutional; POLITICAL SCIENCE / Public Policy / Social Policy; HEALTH & FITNESS / Health Care Issues; HISTORY / United States / 21st Century